2020
DOI: 10.1002/oby.23023
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent Versus Continuous Energy Restriction for Weight Loss and Metabolic Improvement: A Meta‐Analysis and Systematic Review

Abstract: Objective This study aimed to evaluate the effects of intermittent energy restriction (IER; only for 2‐3 d/wk) versus continuous energy restriction (CER) on weight loss and metabolic outcomes in adults with overweight or obesity. Methods Methods included searching databases from the last decade to December 18, 2019, for randomized controlled trials (RCTs) that assessed weight loss and metabolic outcomes in IER and CER. RevMan version 5.3 software was used for statistical analysis of the data. The effect sizes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
72
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(80 citation statements)
references
References 49 publications
8
72
0
Order By: Relevance
“…As with previous studies of IER [ 26 28 ], we detected little difference between the efficacy of the 5:2 and the active control condition. Although the 5:2 diet approach is expected to be more ‘forgiving’ than most other IER approaches, adherence to 5:2 declined from some 80% at 6 weeks to some 20% at one year.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…As with previous studies of IER [ 26 28 ], we detected little difference between the efficacy of the 5:2 and the active control condition. Although the 5:2 diet approach is expected to be more ‘forgiving’ than most other IER approaches, adherence to 5:2 declined from some 80% at 6 weeks to some 20% at one year.…”
Section: Discussionsupporting
confidence: 90%
“…Narrative reviews of IER [ 12 14 ] draw heavily on animal data and highlight the paucity of definitive human trials, but several studies evaluated stricter versions of IER in humans [ 11 , 15 27 ]. Typically, participants were asked to restrict energy to 25% of their usual daily calories every other day (‘alternate day fasting’) or on two consecutive days per week [ 28 ] sometimes after a period on a very-low energy diet. Participants were usually also asked to use prescriptive diets on non-fasting days.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Eleven meta-analyses were included ( Figure ) (justification for excluded full-text articles available in eTable 2 in the Supplement ). 5 , 6 , 7 , 8 , 22 , 23 , 24 , 25 , 26 , 27 Eligible meta-analyses included 130 RCTs (45 unique RCTs) with a median (IQR) sample size per RCT of 38 (24-69) studies and a follow-up period of 3 (2-5) months ( Table 1 ). The quality of meta-analyses assessed using AMSTAR-2 found that none were rated as high confidence, 7 (64%) as moderate confidence, and 4 (36%) as low confidence ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…The impact of obesity on people’s well-being and the resulting increase in the risk of chronic non-communicable diseases [ 1 , 2 , 3 , 4 ] are well-known facts about the condition. A combination of caloric restriction and physical exercise are the key components to observing a weight loss of approximately 10% in the sixth month of intervention [ 5 ].…”
Section: Introductionmentioning
confidence: 99%